Creep Behaviors of Methane Hydrate-Bearing Frozen Sediments - Yanghui Li; Peng Wu; Xiang Sun; Weiguo Liu; Yongchen Song; Jiafei Zhao (Energies, 2019)
Creep behaviors of methane hydrate-bearing frozen specimens are important to predict the long-term stability of the hydrate-bearing layers in Arctic and permafrost regions. In this study, a series of creep tests were conducted, and the results indicated that: (1) higher deviator stress (external load) results in larger initial strain, axial strain, and strain rate at a specific elapsed time. Under low deviator stress levels, the axial strain is not large and does not get into the tertiary creep stage in comparison with that under high deviator stress, which can be even up to 35% and can cause failure; (2) both axial strain and strain rate of methane hydrate-bearing frozen specimens increase with the enhancement of deviator stress, the decrease of confining pressure, and the decrease of temperature; (3) the specimens will be damaged rather than in stable creep stage during creeping when the deviator stress exceeds the quasi-static strength of the specimens.